Lacunar Stroke Lesion Extent and Location and White Matter Hyperintensities Evolution 1 Year Post-lacunar Stroke - Valdés Hernández, Maria del C.; Grimsley-Moore, Tara; Sakka, Eleni; Thrippleton, Michael J.; Chappell, Francesca M.; Armitage, Paul A.; Makin, Stephen; Wardlaw, Joanna M. (Frontiers in Neurology, 2021)
Lacunar strokes are a common type of ischemic stroke. They are associated with long-term disability, but the factors affecting the dynamic of the infarcted lesion and the brain imaging features associated with them, reflective of small vessel disease severity, are still largely unknown. We investigated whether the distribution, volume and 1-year evolution of white matter hyperintensities (WMH) relate to the extent and location of these infarcts, accounting for vascular risk factors. We used imaging and clinical data from all patients (n=118, mean age 64.9 (SD 11.75) years old) who presented to a regional hospital with a lacunar stroke within 2010 and 2013 and consented to participate in a study of stroke mechanisms. All patients had a brain MRI scan at presentation, and 88 had another scan 12 months after. Acute lesions (i.e., recent small subcortical infarcts, RSSI) were identified in 79 patients and lacunes in 77. Number of lacunes was associated with baseline WMH volume (B=0.370, SE=0.0939, P=0.000174). RSSI volume was not associated with baseline WMH volume (B=3.250, SE=2.117, P=0.129), but predicted WMH volume change (B= 2.944, SE=0.913, P=0.00184). RSSI location was associated with the spatial distribution of WMH and the pattern of 1-year WMH evolution. Patients with the RSSI in the centrum semiovale (n=33) had significantly higher baseline volumes of WMH, recent and old infarcts, than patients with the RSSI located elsewhere (median 33.69, IQR [14.37 50.87] ml, 0.001≤P≤0.044). But patients with the RSSI in the internal/external capsule/lentiform nucleus experienced higher increase of WMH volume after a year (n=21, median [IQR] from 18 [11.70 31.54] ml to 27.41 [15.84 40.45] ml). Voxel-wise analyses of WMH distribution in patients grouped per RSSI location revealed group differences increased in the presence of vascular risk factors, especially hypertension and recent or current smoking habit. In our sample of patients presenting to the clinic with lacunar strokes, lacunar strokes extent influenced WMH volume fate; and RSSI location and WMH spatial distribution and dynamics were intertwined, with differential patterns emerging in the presence of vascular risk factors. These results, if confirmed in wider samples, open potential avenues in stroke rehabilitation to be explored further.